Monitoring the oxygen level in the Szarvas-Kákafok Deadarm - Csizmarik, Gábor; Ligetvári, Ferenc; Juhász, Csaba; Simándi, Péter (Acta Agraria Debreceniensis, 2010)
The water quality of the Szarvas-Békésszentandrás Dead Körös is generally meso-eutrophic, and meso-saprobic. However, particularly under higher temperature conditions, the water body may change toward the eutrophic state, even algal blooms could be observed previously. The present measurements were conducted during a two week period, twice a day. Three water samples were taken horizontally, from the surface, bottom and the middle of the water body. The samples were examined in situ. The oxygen content, the temperature, the pH and the conductivity were measured by potentiometric methods. Increasing pH was detected in correlation to the temperature, which indicated a rising photosynthetic activity. Also, the O2 concentration showed high variations, especially, when the fresh water supply from the river was stopped, due to a small flood in the river Körös. These results indicate the increasing eutrophication processes in the deadarm, and the high load and instability of the ecosystem.